Next‐generation sequencing in a series of 80 fetuses with complex cardiac malformations and/or heterotaxy. Issue 12 (10th November 2020) - Liu, Hui; Giguet‐Valard, Anna‐Gaëlle; Simonet, Thomas; Szenker‐Ravi, Emmanuelle; Lambert, Laetitia; Vincent‐Delorme, Catherine; Scheidecker, Sophie; Fradin, Mélanie; Morice‐Picard, Fanny; Naudion, Sophie; Ciorna‐Monferrato, Viorica; Colin, Estelle; et al.
Abstract: Herein, we report the screening of a large panel of genes in a series of 80 fetuses with congenital heart defects (CHDs) and/or heterotaxy and no cytogenetic anomalies. There were 49 males (61%/39%), with a family history in 28 cases (35%) and no parental consanguinity in 77 cases (96%). All fetuses had complex CHD except one who had heterotaxy and midline anomalies while 52 cases (65%) had heterotaxy in addition to CHD. Altogether, 29 cases (36%) had extracardiac and extra‐heterotaxy anomalies. A pathogenic variant was found in 10/80 (12.5%) cases with a higher percentage in the heterotaxy group (8/52 cases, 15%) compared with the non‐heterotaxy group (2/28 cases, 7%), and in 3 cases with extracardiac and extra‐heterotaxy anomalies (3/29, 10%). The inheritance was recessive in six genes ( DNAI1, GDF1, MMP21, MYH6, NEK8, and ZIC3 ) and dominant in two genes ( SHH and TAB2 ). A homozygous pathogenic variant was found in three cases including only one case with known consanguinity. In conclusion, after removing fetuses with cytogenetic anomalies, next‐generation sequencing discovered a causal variant in 12.5% of fetal cases with CHD and/or heterotaxy. Genetic counseling for future pregnancies was greatly improved. Surprisingly, unexpected consanguinity accounts for 20% of cases with identified pathogenic variants. Abstract : This figure shows the number of fetuses with causal variants identified in a cohort of 80 cases with congenital heart defects and/or heterotaxy after sequencing their DNA by next‐generation sequencing with a large panel of cardiac genes.